2014
DOI: 10.1155/2014/341734
|View full text |Cite
|
Sign up to set email alerts
|

Day-Ahead Crude Oil Price Forecasting Using a Novel Morphological Component Analysis Based Model

Abstract: As a typical nonlinear and dynamic system, the crude oil price movement is difficult to predict and its accurate forecasting remains the subject of intense research activity. Recent empirical evidence suggests that the multiscale data characteristics in the price movement are another important stylized fact. The incorporation of mixture of data characteristics in the time scale domain during the modelling process can lead to significant performance improvement. This paper proposes a novel morphological compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…He et al [26] proposed a wavelet decomposed ensemble model for the crude oil market and found the improved performance of the proposed algorithm against the benchmark models [26]. Zhu et al [27] proposed the morphological component analysis-based forecasting model and found improved forecasting accuracy in the crude oil markets [27]. Li et al [28] proposed a wavelet denoising ARMA model ensembled by least square support vector regression.…”
Section: Multiscale Analysis In the Energy Marketsmentioning
confidence: 99%
“…He et al [26] proposed a wavelet decomposed ensemble model for the crude oil market and found the improved performance of the proposed algorithm against the benchmark models [26]. Zhu et al [27] proposed the morphological component analysis-based forecasting model and found improved forecasting accuracy in the crude oil markets [27]. Li et al [28] proposed a wavelet denoising ARMA model ensembled by least square support vector regression.…”
Section: Multiscale Analysis In the Energy Marketsmentioning
confidence: 99%